1988
DOI: 10.1007/bf00451282
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neuroleptic on-drug response in schizophrenic in-patients by EEG

Abstract: The subjects were 34 acutely ill in-patients who met the RDC criteria of schizophrenic psychosis, and 4 EEGs were recorded from each patient before, 2 h and 24 h after oral intake of a single dose of 150 mg perazine, and on the 28th day of the neuroleptic treatment period. As a criterion of clinical response a decrease of at least 66% in the schizophrenia-specific sum score of the Brief Psychiatric Rating Scale on day 28 relative to the baseline value was decided upon. The EEGs were assessed using a newly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moore et al 68 observed that an increase of alpha after 6 weeks of treatment with haloperidol or remoxipride was associated with a favorable clinical response. Other studies comparing responders (R) and nonresponders (NR) to treatment with neuroleptics reported an increase of alpha activity only in R 57,69 and changes in the opposite direction in NR. 57 Our group used the test dose procedure to predict short-term response to treatment with either haloperidol or clopentixol in 29 patients with schizophrenia.…”
Section: Prediction Of Clinical Response To Treatment With Psychotropic Drugsmentioning
confidence: 96%
“…Moore et al 68 observed that an increase of alpha after 6 weeks of treatment with haloperidol or remoxipride was associated with a favorable clinical response. Other studies comparing responders (R) and nonresponders (NR) to treatment with neuroleptics reported an increase of alpha activity only in R 57,69 and changes in the opposite direction in NR. 57 Our group used the test dose procedure to predict short-term response to treatment with either haloperidol or clopentixol in 29 patients with schizophrenia.…”
Section: Prediction Of Clinical Response To Treatment With Psychotropic Drugsmentioning
confidence: 96%
“…Ulrich et al 91 focused on the individuation of alpha and non-alpha epochs (i.e. relative power spectrum density of alpha-band > or < 50%) in acutely ill, drug-free patients.…”
Section: Resultsmentioning
confidence: 99%
“…At baseline theta power, either low 86 or high 87 was related to a favorable treatment outcome. A high alpha power predicted a poorer response in most of the studies 66,86,87,[89][90][91] ; moreover, alpha functional connectivity in frontal and temporal regions was inversely related to response 93 . A diminished betapower on a pre-treatment RS-EEG was related to a worse treatment outcome 66,85,86,90,93 , such as a reduced functional connectivity after treatment 93 .…”
Section: Prediction Of Response To Ap With Eeg Featuresmentioning
confidence: 91%